IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN SUPPLIER AC TERBAIK MENGGUNAKAN METODE MOORA STUDI KASUS: PT. TRIPTA KARYA KONSULTINDO - Heru Lukas; Intan Kumalasari (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
PT. Tripta Karya Konsultindo faces challenges in selecting AC suppliers due to a manual, time-consuming, and subjective evaluation process. This study develops a web-based decision support system using the MOORA method to evaluate suppliers based on price, quality, delivery time, experience, and warranty. The results show that the system improves the supplier selection process by providing faster, more objective, transparent, and accountable decision-making through automatic ranking calculations.